(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
This article analyzes the issues of enhancing the economic and ecological significance of rainfed (non-irrigated) lands in the agriculture of the Republic of Uzbekistan, as well as improving the system for assessing their normative value. The study examines modern approaches to determining the normative value, taking into account the meliorative condition, agro-climatic factors, and productivity level of rainfed lands.